Statistical Analysis to View Information Regarding The Influence of Brand Image, Satisfaction, Word of Muoth, and Price on The Purchase Decision of Avanza Brand Cars (Case Study of Showroom Consumers Fahmi's Used Car) - Asri Winaldi Ritonga; Rizki Syahputra; Abd. Halim (JINAV: Journal of Information and Visualization, 2023)
The purpose of this study was to analyze the influence of brand image, satisfaction, word of mouth and price on purchasing decisions for an Avanza brand car (a case study on consumers of Fahmi's used car showroom). This type of research is quantitative in nature, and the place for conducting the research is in the Fahmi Used Car Showroom. The research population is consumers of Fahmi's Used Car Showroom taken from September-November 2022 as many as 58 people. Samples were taken using a saturated sampling technique. Therefore,then all populations become the object of research, namely as many as 58 people. The research results show that Brand Image positive and significant effect on Buying decision. Satisfaction has a positive and significant effect on Buying decision.Word Of Mouth positive and significant effect on Buying decision.Price has a positive and significant effect on Buying decision. Brand image, satisfaction,word of mouth and price simultaneously positive and significant effect on Buying Decisions for Avanza Brand Cars at Fahmi's Used Car Showroom Consumers. The results of the analysis of the coefficient of determination of 0.793 means that purchasing decisions can be explained by brand image, satisfaction,word of mouth and a price of 79.3%.